Cholera Treatment in Malnourish Children - Atif Amin, Baig; Chandrika, Murugaiah; Hassanain, Al-Talib; Shanthi Bavani V, Raja Mohan (2018)
Cholera is an extremely virulent disease that can kill within hours if left untreated; it is an infectious disease that can cause severe diarrhea and dehydration. Cholera is transmitted mainly through contaminated water and food. Children are the most vulnerable to infection. Most cases need rapid treatment with intravenous fluids and antibiotics. The real danger of cholera is the loss of liquid and nutrients from the child’s body. Malnutrition in children with cholera is common in under developed countries. Severe malnutrition remains an important problem in cholera cases. Liquid and nutrition lost can cause dehydration and malnutrition. It is recommended that drink lots of liquids and oral rehydration salts (ORS), properly mixed with clean water from a safe source, and take zinc tablets or syrup for 10–14 days. ORS is a special combination of dry salts that is mixed with water to replace the fluids lost due to diarrhoea. At least 1/4 to 1/2 of a large (250-millilitre) cup of the ORS drink after each watery stool is needed in a child under the age of 2 years, and at least 1/2 to 1 whole large (250-millilitre) cup of the ORS drink after each watery stool in a a child aged 2 years or older. An effective oral rehydration solution for malnourish children can be made using food supplements which contain starches and/ or sugars as a source of glucose and energy, some sodium and some potassium; such as gruels, carrot soup, rice water (congee), and banana or other non-sweetened mashed fruit which provide potassium. Emphasis should be given in to improve nutrition that is the most effective forms of overcoming malnutrition. It has to be taken note that breastfeeding can reduce rates of malnutrition and death in children. Government in the affected countries should put more efforts to promote the practice to increase the rates of breastfeeding. In young children, together with to breast milk, nutritious food should be provided in children between six months and two years of age. It is recommended that supplementation of a number of micronutrients to women during pregnancy and among young children in the developing world could effectively nourish malnutrition in cholera patient.